2009
DOI: 10.7326/0003-4819-150-10-200905190-00003
|View full text |Cite
|
Sign up to set email alerts
|

Splint for Base-of-Thumb Osteoarthritis

Abstract: Programme Hospitalier de Recherche Clinique National.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
121
1
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 27 publications
0
121
1
16
Order By: Relevance
“…The identification of phenotypes at other sites, such as the thumb base and patellofemoral joint, has led to greater understanding about the etiology and presentation of OA at these locations 8, 9. Early research targeting treatments for these sites has shown some positive outcomes 10, 11, and this approach may also be appropriate for different forms of foot OA.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of phenotypes at other sites, such as the thumb base and patellofemoral joint, has led to greater understanding about the etiology and presentation of OA at these locations 8, 9. Early research targeting treatments for these sites has shown some positive outcomes 10, 11, and this approach may also be appropriate for different forms of foot OA.…”
Section: Introductionmentioning
confidence: 99%
“…Le port de cette attelle est surtout recommandé la nuit. L'étude de Rannou et al, menée sur 112 patients, a comparé le port d'une attelle nocturne à un traitement classique de la rhizarthrose chez des patientes symptomatiques [20]. La compliance dans cet essai du port de l'orthèse était de plus de 80 %.…”
Section: Traitementunclassified
“…L'évaluation clinique s'est faite au premier mois puis jusqu'à un an d'évolution sur des scores de douleur et des scores de handicap. À douze mois, tous les indices concernant la douleur et le handicap favorisent le port de l'orthèse avec une différence significative par rapport au groupe n'en n'ayant pas porté [20]. En revanche, cette orthèse n'augmente pas à la force de préhension de la pince pouce-index [20].…”
Section: Traitementunclassified
“…Имеются различные рекомендации, касающиеся ношения ортезов: одни авторы считают необходимым их использование в дневное время, другие -в ночное. Умень-шение боли при длительном применении ортезов отмечено в двух исследованиях [19,20].…”
unclassified